Antano Baranausko dienoraštis: rašymo ir leidimo istorija - Andriukonis, Tomas (Literatūra, 2010)
The article considers Antanas Baranauskas’s diary – the manuscript of its text and its three publications. During careful examination of the diary making principles there will be brought up an issue of the Baranauskas’s text boundaries – how they are clearly defined, where they (maybe) are, how they have been considered and how they have been built in the diary publications. A more careful study of the diary discloses an ambivalent genre of Barnauskas’s text – started as a diary, in the end it looks more like an autobiography. Diary’s re-writing can be considered as a separate issue, taking into consideration that it makes more complicated the issue of the text boundaries, also it makes correction in the diary’s reading strategy.